2006
DOI: 10.5194/nhess-6-761-2006
|View full text |Cite
|
Sign up to set email alerts
|

Geology, glacier retreat and permafrost degradation as controlling factors of slope instabilities in a high-mountain rock wall: the Monte Rosa east face

Abstract: Abstract. The Monte Rosa east face, Italian Alps, is one of the highest flanks in the Alps (2200-4500 m a.s.l.). Steep hanging glaciers and permafrost cover large parts of the wall. Since the end of the Little Ice Age (about 1850), the hanging glaciers and firn fields have retreated continuously. During recent decades, the ice cover of the Monte Rosa east face experienced an accelerated and drastic loss in extent. Some glaciers have completely disappeared. New slope instabilities and detachment zones of gravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
159
0
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 208 publications
(165 citation statements)
references
References 14 publications
4
159
0
2
Order By: Relevance
“…The east face of Monte Rosa extends from about 2200 m to over 4600 m a.s.l., and was the site of two spectacular avalanches in 2005 and 2007 (Fischer et al 2006). The slope increases upward, reaching greater than 55 • in the exposed gneissic bedrock sections and greater than 40 • in the sections with glaciers (figure 12).…”
Section: (C) Monte Rosa Alpsmentioning
confidence: 99%
See 3 more Smart Citations
“…The east face of Monte Rosa extends from about 2200 m to over 4600 m a.s.l., and was the site of two spectacular avalanches in 2005 and 2007 (Fischer et al 2006). The slope increases upward, reaching greater than 55 • in the exposed gneissic bedrock sections and greater than 40 • in the sections with glaciers (figure 12).…”
Section: (C) Monte Rosa Alpsmentioning
confidence: 99%
“…Studies based on sequential historical photographs have shown that the ice cover on the east face of the mountain changed a little during the twentieth century until about 1980, when it began to rapidly decrease (Haeberli et al 2002;Fischer et al submitted b). Slope instability involving both ice and rock increased around 1990 and has continued to the present (Fischer et al 2006 The 2005 event was a large ice avalanche (1.1 × 10 6 m 3 ) that initiated from a steep glacier terminating at 3500 m a.s.l. and reached the foot of the face, where a large supraglacial lake had formed in 2002, but had drained in 2003 (figure 12).…”
Section: (C) Monte Rosa Alpsmentioning
confidence: 99%
See 2 more Smart Citations
“…The possibility that failure was triggered by warming of ice in bedrock joints reducing the stability of the rock mass (e.g. Dramis et al, 1995;Haeberli et al, 1997;Davies et al, 2001;Fischer et al, 2006;Gruber and Haeberli, 2007) seems unlikely as failure occurred during cold periods associated with widespread permafrost, but cannot be excluded owing to the low precision of the exposure ages.…”
Section: Paraglacial Landscape Modificationmentioning
confidence: 99%